A Subseasonal Regime Approach for Assessing Intra-annual Variability of Evapotranspiration and Application to the Upper Colorado River Basin - Chen, Jiancong; Dafflon, Baptiste; Wainwright, Haruko M.; Tran, Anh Phuong; Hubbard, Susan S. (Frontiers in Water, 2022)
Evapotranspiration (ET), an important component of watershed energy and water balance, is strongly influenced by gradual climate change and fluctuations in meteorological conditions, such as earlier snowmelt and occurrence of droughts. While numerous studies have investigated how climate change influences the inter-annual variability of ET, very few studies have focused on quantifying how subseasonal events control the intra-variability of ET. In this study, we have developed the concept of subseasonal regimes, determined statistically using Hidden Markov Models based on meteorological conditions. This concept offers a number of advantages, because it can holistically incorporate the onset of multiple watershed dynamics. We tested the value of subseasonal regimes for quantitatively characterizing the variability of seasonal and subseasonal events, including the onset of snow accumulation, snowmelt, growing season, monsoon, and defoliation. We examined how ET varied as a function of the timing of these events within a year and across six watersheds in the region. We found that the variability of annual ET across these six sites is much less significant than the variability inherent in hydroclimate attributes at the sites, indicating complex nonlinear interactions between ET and other hydroclimate processes. Subseasonal ET, defined as the total ET during a given subseasonal regime, provides a quantitative measure of intra-annual variability of ET. Our study suggests that earlier snowmelt tends to increase springtime ET rapidly, particularly as a result of higher solar radiation at this time of year. Depending on monsoon onset, earlier snowmelt can trigger long-lasting fore-summer drought conditions that decrease subseasonal ET significantly or lead to higher cumulative ET when monsoons arrive earlier. Both snowmelt and monsoon timing influence regime transitions and durations, and annual ET variability is jointly controlled by all subseasonal regimes. Overall, our approach provides an enhanced statistically based framework for quantifying how the timing of subseasonal-event transitions influence ET variability. This improved understanding of how ET varies with the timing of key seasonal and subseasonal events is important for predicting the future impact of climate change on water resources from the Colorado River Basin regions.